Quality culture at Nordic Universities - Nygren-Landgärds, Christina (Taylor and Francis Ltd., 2022)
This study aimed to investigate common features and ways of understanding quality culture (QC) within higher education institutions (HEIs) in Nordic countries. While the concept of QC is commonly accepted and often used, its meaning is not always clear. This paper focuses on how Nordic universities frame QC in their internal documentation. The Nordic context was chosen due to the close cooperation on quality issues that characterise HEIs within the Nordic region. The discussion section of this paper outlines QC in relation to quality assurance (QA) among HEIs within the European and Nordic regions. Sixteen universities participated in the study by sharing documents describing their QCs. The data were analysed using qualitative content analysis and discussed from different perspectives, such as regarding how the universities use the concept of QC and how QC is created. Based on the results, a model was created that provides an overview of how QC emerges and how the concept is implemented in documentation. It is hoped that the results will both contribute useful input to the ongoing collaboration on quality issues among HEIs in the Nordic region and will also be useful in enhancing QC at universities in other regions.